PENGEMBANGAN MEDIA PROMOSI RUMAH MAKAN RA.MEN SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Putra, Rio Andika; Riyanto, Darwin Yuwono; Cinantya, Ixsora Gupita (Jurnal Art Nouveau, 2018)
Abstract: Ra.Men restaurant is a growing business in the field of culinary and has stood in the area of Gayungsari Barat, Surabaya since 2014. Restaurants have added value because the products are sold is a tyspical food prouk originating from the country of Japan. For example Ramen and Sushi. For Surabaya environment. Especially the area Gayungsari, Ra.men Restaurant is quite well known by the community and has had a number of customers. But along with the development of time, began many other typical Japanese restaurant that stands in the area Gayungsari, for example Chirashi Sushi and Wasabi Yatai. This is considered to threaten the existence of Restaurant Ra.men long standing. To prevent that it is necessary to make the development of media promotion Ra.Men Restaurant as an effort to increase Brand Loyalty. Qualitative research is conducted by interview, observation, documentation, and study of literature to get the data used as a basis in developing the design concept. The concept of design in the development of media promotion Ra.Men restaurant as an effort to increase brand loyalty is